The investment of time in the recommendations of serious violations of the National Human Rights Commission - Hernández Pérez, Selene (2022)
This research article studies the relationship between time investment and bureaucratic restriction, in the issuance of recommendations of serious violations, issued by the National Human Rights Commission (NHRC), in Mexico, from 2000 to 2019. It is explained that the annual administrative closure of the Commission's work influences the duration of the process of issuing the recommendations, which affects the search for prompt justice and the compensation of the victim. In this way, it is suggested that there is arbitrary, intentional and selective detention on certain complaints, by NHRC personnel. For this purpose, recommendations were analyzed for cases that only denounced one serious incident (as defined by article 88 of the internal regulations of the NHRC). The results showed that the administrative criterion influences the publication of a recommendation, and that as November 15 approaches (administrative year closing date), the recommendations are more likely to be published. It is also possible to observe that the recommendations published on dates far from November 15 tend to have a greater probability of not being published quickly. In order to explain this relationship, a multiple linear regression model was used. The duration of time to reach recommendations was used as the dependent variable. To construct the variable, the number of days was counted from the time the complaint was received to the issuance of a recommendatory document. The main independent variable was the “closeness to the end of the period” that indicates the number of days close to the end of each administrative period of the NHRC (every November 15).